MORPHOLOGICAL CHANGES IN BRAIN STRUCTURES IN ALCOHOLISM (LITERATURE REVIEW) - N.E.Tukhsanova. (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation:The analysis of modern scientific sources on the problem of studying structural changes in the brain during intoxication and alcohol poisoning is carried out. It is emphasized that in all structures of the central nervous system, changes are observed up to atrophy of the cortex and subcortical structures of the brain. There are disorders of microcirculation in the vessels of the brain with the formation of multiple diffuse diapedous hemorrhages.